Role of Vitamins in Pathogenesis and Treatment of Cancers (Kindle, 2023)
Vitamins with antioxidant characteristics have been shown as potential chemopreventive agents because of their roles in quenching free radicals and decreasing oxidative damage to DNA. It has been reported that the major antioxidants are vitamins A, C, E, Betacarotene and Selenium. Findings from retrospective and prospective cohort investigations were highly inconsistent and controversial. However, recent investigations have shown an inverse correlation between the consumption of vitamins in diet and the risk of different cancers.
Keywords: Vitamins; Antioxidants; Nutritional Oncology; Oxidative Stress